2013
DOI: 10.1590/s2317-17822013000400010
|View full text |Cite
|
Sign up to set email alerts
|

Management of dysphagia in Parkinson's disease and amyotrophic lateral sclerosis

Abstract: Compensatory and sensorial maneuvers are more recommended to rehabilitee program in both diseases. The physiopathology of the diseases determined the choice of therapeutic approaches. The disease duration of the patients did not interfere directly in the therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 19 publications
0
35
0
12
Order By: Relevance
“…8 However, it is not always that the subject who has had the disease for a longer duration or is at an older age shows the worst progression or impairments. 13 Oliveira et al, 14 who evaluated the mortality rate of patients with ALS in relation to time, location and gender, did not find significant differences between the percentage of mortality between men and women, and concluded that there was no significant difference between the age associated with time of progression and death. It was clear from our study that subject 1, who has had the disease for two years, was the one who presented fewer sequels, both concerning space and time variables in relation to angular kinematics.…”
Section: Discussionmentioning
confidence: 98%
“…8 However, it is not always that the subject who has had the disease for a longer duration or is at an older age shows the worst progression or impairments. 13 Oliveira et al, 14 who evaluated the mortality rate of patients with ALS in relation to time, location and gender, did not find significant differences between the percentage of mortality between men and women, and concluded that there was no significant difference between the age associated with time of progression and death. It was clear from our study that subject 1, who has had the disease for two years, was the one who presented fewer sequels, both concerning space and time variables in relation to angular kinematics.…”
Section: Discussionmentioning
confidence: 98%
“…21 Furthermore, other studies reported that pharyngeal residues are commonly observed in food of pasty and liquid consistencies. 7,18,22 Based on the data, it was possible to observe that function inefficiency was present in the oral phase and the pharyngeal phases, the most compromised. Due to the motor loss and muscular weakness caused by the disease, the structures elicited for the preparation of the food bolus are also compromised, what may justify the reduced tongue mobility and, consequently, the increased oral transit time.…”
Section: Acta Fisiatr 2016;23(3):120-124mentioning
confidence: 99%
“…7 In the late stages of the disease, the indication of an alternative feeding pathway is required, once, due to the severe dysphagia, the muscle fatigue, and/or respiratory insufficiency the food ingestion solely by the oral pathway become unfeasible, what justifies the relevance of a precise evaluation of deglutition.…”
mentioning
confidence: 99%
See 2 more Smart Citations